Ankaferd Blood Stopper for Controlling Gastrointestinal Bleeding due to Distinct Benign Lesions Refractory to Conventional Antihemorrhagic Measures - Mevlut Kurt; Ibrahim Koral Onal; Meral Akdogan; Murat Kekilli; Mehmet Arhan; Abdurrahim Sayilir; Erkin Oztas; Ibrahim Celalettin Haznedaroglu (Canadian Journal of Gastroenterology)
OBJECTIVE: To assess the hemostatic efficacy of the Ankaferd Blood Stopper (ABS, Ankaferd Health Products Ltd, Turkey) hemostatic agent for controlling gastrointestinal bleeding associated with various benign lesions refractory to conventional antihemorrhagic measures.